2022
DOI: 10.3171/2022.2.focus21789
|View full text |Cite
|
Sign up to set email alerts
|

The role of neurosurgery in the management of tuberous sclerosis complex–associated epilepsy: a systematic review

Abstract: OBJECTIVE Tuberous sclerosis complex (TSC) is an autosomal dominant, multisystem neurocutaneous disorder associated with cortical tubers, brain lesions seen in nearly all patients with TSC, which are frequently epileptogenic. Seizures are often the earliest clinical manifestation of TSC, leading to epilepsy in over 70% of patients. Medical management with antiepileptic drugs constitutes early therapy, but over 50% develop medically refractory epilepsy, necessitating surgical evaluation and treatment. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The excluded patients had a localizable epileptogenic focus on noninvasive monitoring alone and were most likely able to achieve seizure freedom with single-step resection/ablation; therefore, these outcomes were likely underreported as compared with historical studies that included only patients with TSC-associated epilepsy. 8,22,28 In this study, we noted a trend for increasing seizure freedom with longer follow-up. The study was unique because a large single center captured all patients who were observed for a significantly longer period than those included in most reported studies of TSC.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The excluded patients had a localizable epileptogenic focus on noninvasive monitoring alone and were most likely able to achieve seizure freedom with single-step resection/ablation; therefore, these outcomes were likely underreported as compared with historical studies that included only patients with TSC-associated epilepsy. 8,22,28 In this study, we noted a trend for increasing seizure freedom with longer follow-up. The study was unique because a large single center captured all patients who were observed for a significantly longer period than those included in most reported studies of TSC.…”
Section: Discussionmentioning
confidence: 49%
“…If there is clear concordance among the various noninvasive modalities regarding the location of the epileptogenic focus with correlation to a single seizure semiology, resection/ablation of the tuber may proceed without intracranial monitoring. 8,28,34,35 In cases without a dominant tuber or epileptogenic focus but with clear lateralization, unilateral intracranial monitoring is indicated. If no dominant tuber is identified and/or multiple seizure semiologies/discordant data prevail but a regional network is suggested on noninvasive workup, then bilateral intracranial monitoring may be indicated.…”
Section: Sdg Versus Seeg Monitoring In Tsc Patientsmentioning
confidence: 99%
“…96 Seizure reduction can result from destruction of the SOZ, network disconnection by interruption of essential pathways, or network-wide neuromodulation. [97][98][99] A map of the epileptic network can thus be a valuable addition to the presurgical evaluation. Tractography studies based on MRI diffusion tensor imaging can be used to visualize neuronal white matter tracts and provide an anatomic correlate of network paths.…”
Section: Functional Connectivity and The Epileptic Networkmentioning
confidence: 99%
“…96 Seizure reduction can result from destruction of the SOZ, network disconnection by interruption of essential pathways, or network-wide neuromodulation. 97 98 99…”
Section: Functional Connectivity and The Epileptic Networkmentioning
confidence: 99%